2001
DOI: 10.1016/s0896-6273(01)00547-5
|View full text |Cite|
|
Sign up to set email alerts
|

The DRASIC Cation Channel Contributes to the Detection of Cutaneous Touch and Acid Stimuli in Mice

Abstract: Cation channels in the DEG/ENaC family are proposed to detect cutaneous stimuli in mammals. We localized one such channel, DRASIC, in several different specialized sensory nerve endings of skin, suggesting it might participate in mechanosensation and/or acid-evoked nociception. Disrupting the mouse DRASIC gene altered sensory transduction in specific and distinct ways. Loss of DRASIC increased the sensitivity of mechanoreceptors detecting light touch, but it reduced the sensitivity of a mechanoreceptor respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
385
4
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 553 publications
(422 citation statements)
references
References 67 publications
24
385
4
2
Order By: Relevance
“…The asic3 -/-mice were significantly more sensitive (76), which is consistent with the early report showing increased light-touch response in asic3 -/-mice (45). These data strongly suggest the participation of ASIC3 in touch perception.…”
Section: Roles In Mechanosensationsupporting
confidence: 92%
See 3 more Smart Citations
“…The asic3 -/-mice were significantly more sensitive (76), which is consistent with the early report showing increased light-touch response in asic3 -/-mice (45). These data strongly suggest the participation of ASIC3 in touch perception.…”
Section: Roles In Mechanosensationsupporting
confidence: 92%
“…For example, in the isolated skin-nerve preparation, the response to a drop of pH to 5.0 was reduced in C fibers of ASIC3 null animals. The loss of ASIC3 increased the sensitivity of mechanoreceptors to light touch, but it reduced the sensitivity of a mechanoreceptor to respond to a noxious pinch and decreased the responses of acid-and noxious heat-sensitive nociceptors (45). In contrast, Chen et al (51) found an increased sensitivity to thermal, mechanical, and acidic stimuli in ASIC3 knockout mice but detected no alterations in hypersensitivity after capsaicin or carrageenan treatment.…”
Section: Cutaneous Nociceptionmentioning
confidence: 94%
See 2 more Smart Citations
“…Therapeutic potential-Since activation of ASIC3 has been implicated in various pain processes [46,51,62,63], APETx2 may be a useful analgesic agent in the treatment or prevention of pain in peripheral sensory system. However, its lack of inhibition of sustained ASIC3 current suggests that it may not be effective in suppressing the chronic pain stimuli.…”
Section: Apetx2mentioning
confidence: 99%